2013
DOI: 10.1177/1933719112459236
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte—Macrophage Colony-Stimulating Factor Enhances the Humoral Immune Responses of Mouse Zona Pellucida 3 Vaccine Strategy Based on DNA and Protein Coadministration in BALB/c Mice

Abstract: We recently demonstrated that co-administration of mouse zona pellucida 3 (mZP3) DNA and protein vaccine enhanced the contraception of mice by increasing humoral immune responses. In this study, we try to use granulocyte-macrophage colonystimulating factor (GM-CSF) to further improve the humoral immune responses induced by mZP3 DNA and protein co-administration. BALB/c mice were intranasally pre-injected with GM-CSF 4 days before co-administration. Compared to DNA and protein coadministration without GM-CSF, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Modified FCA has also been used as a safe, effective substitute for FCA (Lyda et al 2005). Recent studies have also shown that intra-nasal delivery of four doses of mouse ZP3 result in a significant reduction of reproductive output in mice (Ma et al 2012;Kadir et al 2013). In parallel, several newer alternative reagents, such as purified and/or receptor-specific adjuvants (e.g.…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
“…Modified FCA has also been used as a safe, effective substitute for FCA (Lyda et al 2005). Recent studies have also shown that intra-nasal delivery of four doses of mouse ZP3 result in a significant reduction of reproductive output in mice (Ma et al 2012;Kadir et al 2013). In parallel, several newer alternative reagents, such as purified and/or receptor-specific adjuvants (e.g.…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
“…One hundred microliters of DMSO was added to each well, and the absorbance was measured at 570 nm using a microplate spectrophotometer (Benchmark Plus™, Bio-Rad). Data are reported as stimulation index, calculated as the mean absorbance of triplicate wells stimulated with an antigen, and divided by the mean absorbance of triplicate wells stimulated with the medium (A antigen /A control , used as control) ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mucosal vaccination has the advantage of needle-free administration, induces both systemic and mucosal immune responses, and can be used for mass vaccination ( 25 ). Our previous studies showed that nasal immunization induced both IgA and IgG Ab responses to mZP3 in mouse models ( 27 , 28 ). In order to protect DNA from degradation, chitosan, a biodegradable cationic polysaccharide, was used to encapsulate the plasmid DNA as in our previous studies ( 14 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, administration of ZP3 antibody can inhibit the interac-tion between sperm and eggs [3]. Aulanni'am and Sumitro found that ZP3 antibody was an effective inhibiting interaction between sperm and eggs in vivo fertilization by disrupting ZP3 binding to its ligand [4]. ZP3antibody based-contraception is also permanent and reversible [5].…”
Section: Introductionmentioning
confidence: 99%
“…Development of immunocontraception of pellucid zone among mammals, both native and recombinant, is widely developed from cows, goats, or rabbits. It shows the interspecific reaction of antibody on ZP3 [4]. Mubarakati et al produced ZP3 antibody from human blood (mab-hZP3) as a potential candidate for immunocontraception, but its side effect on folliculogenesis still need to be further studied [12].…”
Section: Introductionmentioning
confidence: 99%